(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article highlights the methods of family education and development of children with hearing impairments of preschool age and effective ways of cooperation between parents of children with hearing impairments of a multidisciplinary specialized preschool educational organization, the importance of early correctional work for parents.